KOMPETENSI BUDAYA DAN SUKSES BISNIS : BAGAIMANA PELAKU BISNIS INDONESIA MEMAHAMI PERBEDAAN FORMAT BUDAYA BISNIS ? - Edi Prasetyo Nugroho (Journal of Indonesian Economy and Business (JIEB), 1998)
One of the major business challenges in the era of global business is howbusiness doers decide their own position in the term of business culture. This issuewill be more important in the years ahead, since strategically the ability of businessdoers to exist in global competition atmosphere will depend on the dialog of theirown business culture with the other business cultures. Generally speaking, there's noroom for short-sighted-syndrome in cultural dialog to success in business. Thisarticle discusses the perspective of Indonesian business doers in understanding theirown business culture and other business cultures. We use these point of views, sincesome business cultures practically affecting the way Indonesian business peopleappreciate their own work environment. A good appreciation toward workenvironment will lead to success in doing business.